Über das Altern und das Alter. Versuch einer Orientierung für die Seelsorge - HÉZSER, Gábor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
About elders and old-age. Attempt of Orientation for the Pastoral Counseling. In the introduction the study presents the biological, physical, medical and psycho-logical aspects of old age. It also focuses on the religious and philosophical changes. Among the psychological particularities of gerontology it presents the competencies, which are the “privileges” of old age and the process of getting old: wisdom, social and financial freedom, human relationships, experience. It emphasizes that the process of getting old differs from men to women, enumerates the characteristics of the two genders, highlighting the differences. A few examples of different types of attitude towards the changing feelings about life: loneliness, solitude, grief, pain, feeling of being dependent and vulnerable. Old people change their attitude towards religion, spirituality, it gets deeper, as the spiritual experience of “belonging to God”.